A Comparative Analysis of Pricing and Reimbursement of Cystic Fibrosis Transmembrane Conductance Regulator Modulators in Europe - Abdallah, Khadidja; De Boeck, Kris; Dooms, Marc; Simoens, Steven (Frontiers in Pharmacology, 2021)
Objectives: Cystic fibrosis transmembrane conductance regulator (CFTR) modulators, Kalydeco® (ivacaftor), Orkambi® (lumacaftor/ivacaftor) and Symkevi® (tezacaftor/ivacaftor), have substantially improved patients’ lives yet significantly burden healthcare budgets. This analysis aims to compare pricing and reimbursement of aforementioned cystic fibrosis medicines, across European countries. Methods: Clinical trial registries, national databases, health technology assessment reports and grey literature of Austria, Belgium, Denmark, France, Germany, Ireland, Poland, Spain, Sweden, Switzerland, Netherlands, the United Kingdom were consulted. Publicly available prices, reimbursement statuses, economic evaluations, budget impact analyses and managed entry agreements of CFTR modulators were examined. Results: In Belgium, lowest list prices were observed for Kalydeco® (ivacaftor) and Symkevi® (tezacaftor/ivacaftor) at €417 per defined daily dose (DDD) and €372 per average daily dose (ADD), respectively. Whereas, Switzerland had the lowest price for Orkambi® (lumacaftor/ivacaftor) listed at €309 per DDD. Spain had the highest prices for Kalydeco® (ivacaftor) and Symkevi® (tezacaftor/ivacaftor) at €850 per DDD and €761 per ADD, whereas Orkambi® (lumacaftor/ivacaftor) was most expensive in Poland at €983 per DDD. However, list prices were subject to confidential discounts and likely varied from actual costs. In all countries, these treatments were deemed not to be cost-effective. The annual budget impact of the CFTR modulators varied between countries and depended on factors such as local product prices, size of target population, scope of costs and discounting. However, all modulators were fully reimbursed in ten of the evaluated countries except for Sweden and Poland that, respectively, granted reimbursement to one and none of the therapies. Managed entry agreements were confidential but commonly adopted to address financial uncertainties. Conclusion: Discrepancies concerning prices, reimbursement and access were detected for Kalydeco® (ivacaftor), Orkambi® (lumacaftor/ivacaftor) and Symkevi® (tezacaftor/ivacaftor) across European countries.